Revisiting field: Specialized knowledge in secondary school science and humanities discourse - Martin, J. R. (Onomázein, 2017)
This paper revisits the register variable field in systemic functional linguistics (SFL), in relation to the concept of ‘semantic density’ in Legitimation Code Theory (LCT). Re-interpreta-tions of the specialized meaning construing disciplinarity are proposed, from the perspective of the ideational, interpersonal and textual metafunctions—highlighting technicality, iconi-zation and aggregation respectively. The term ‘mass’ is suggested as a cover term for these resources. The paper contributes to an ongoing dialogue between SFL and LCT in relation to research on secondary school history and biology discourse in Australian schools, an increa-singly productive exercise in transdisciplinary research.